Marine plastic governance driven by progressive standards: against the backdrop of global plastics treaty negotiations - Xu, Bohan (Frontiers in Marine Science, 2025)
Marine plastic governance has become one of the most pressing challenges facing the marine environment. The existing international legal framework is inadequate to address this issue, characterized by a lack of systemic comprehensiveness and targeted measures. Furthermore, imperfect implementation and monitoring mechanisms make it difficult to ensure effective compliance by states. Although the “Legally Binding International Instrument on Plastic Pollution (including Marine Plastic Pollution)” (hereinafter referred to as the Global Plastics Treaty) proposes a series of ambitious governance measures, its negotiations reached a deadlock after the Geneva session in August 2025. This stalemate underscores the conflicting interests and divergent views among nations and stakeholder groups regarding global plastic governance. This paper analyzes perspectives on marine plastic governance drawn from existing treaties and literature, proposes principled constraints together with feasible technical solutions and pathways, and offers potential options for the next phase of the Global Plastics Treaty negotiations. The analysis demonstrates that effective marine plastic governance depends on pragmatic political commitment and the active cooperation of all nations. The Global Plastics Treaty should adopt a progressive, standards-driven framework that implements the principle of common but differentiated responsibilities (CBDR) through political commitments to appropriate standards, supported by technical and financial assistance. The non-regression principle should be implemented through mandatory national reporting and unified monitoring. Building upon these two principles, marine plastic governance can be strengthened through the development, adoption, and implementation of progressive standards.